Molecular metal oxides for electrochemical energy storage - Mughal, Neelam Sahar (2021)
The work presented in this thesis is a multifaceted approach to the fabrication of low cost and high performance composite electrode materials. The incorporation of polyoxometalates (POMs) within carbonaceous materials represents an important platform for creating bespoke electrode materials. Both materials have high degrees of tuneability with respect to the structure, electrochemical performance and surface chemistry. Chapter 1 provides an overview into the evolution of Li-ion battery technology. This section highlights how the concerted efforts of battery chemists since the discovery of Alessandro Volta’s ‘voltaic pile’ have led to the commercialisation of batteries in today’s society. The challenges of Li-ion technology moving forward are addressed and POMs are subsequently introduced as a promising candidate for the batteries of the future. The electrochemical behaviour of a library of plenary and modified POMs is assessed. The obtained redox profiles are examined in detail for aqueous and organic solvents, including a battery electrolyte. The tuneable and versatile nature of the studied POMs is discussed with respect to addenda metal substation, transition metal substitution and hybridisation. Interesting cation – dependent electrochemistry in the presence of metal ions (Li+/Na+/Mg2+) is also presented. The proceeding chapter describes the preparation of a surface modified conductive carbon black, by way of chemical oxidation. The material is characterised and compared to its unmodified analogue. POMs are incorporated on to the two different matrices. The composite materials are analysed and tested using cyclic voltammetry in a range of different solvents, including a battery electrolyte. The effect of surface oxidation of carbon on the retention of POMs during electrochemical cycling is explored. Subsequently, the penultimate chapter corroborates the electrochemical performance of the POM/carbon composites observed thus far. The unmodified carbon POM composite and the surface oxidised carbon POM analogue are used as the positive electrode in lithium metal test batteries. The performance is assessed with regards to reversible redox POM chemistry and achieving capacities close to that of the calculated theoretical value. For batteries, one size does not fit all, and as such, different experimental parameters and electrode preparation techniques are probed to inform future experimental design. The final chapter explores a novel method for the preparation of POM-activated carbon based composite electrodes. This approach seeks to apply the principles of template design to prepare dimensionally controlled porous architectures with POMs encapsulated in the pores. Such a method, if successfully controlled, could assure mechanically robust redox active composite materials for energy storage applications.